ORAI Calcium Channels: Regulation, Function, Pharmacology, and Therapeutic Targets - Hussein N. Rubaiy (MDPI AG, 2023)
The changes in intracellular free calcium (Ca2+) levels are one of the most widely regulators of cell function; therefore, calcium as a universal intracellular mediator is involved in very important human diseases and disorders. In many cells, Ca2+ inflow is mediated by store-operated calcium channels, and it is recognized that the store-operated calcium entry (SOCE) is mediated by the two partners: the pore-forming proteins Orai (Orai1-3) and the calcium store sensor, stromal interaction molecule (STIM1-2). Importantly, the Orai/STIM channels are involved in crucial cell signalling processes such as growth factors, neurotransmitters, and cytokines via interaction with protein tyrosine kinase coupled receptors and G protein-coupled receptors. Therefore, in recent years, the issue of Orai/STIM channels as a drug target in human diseases has received considerable attention. This review summarizes and highlights our current knowledge of the Orai/STIM channels in human diseases and disorders, including immunodeficiency, myopathy, tubular aggregate, Stormorken syndrome, York platelet syndrome, cardiovascular and metabolic disorders, and cancers, as well as suggesting these channels as drug targets for pharmacological therapeutic intervention. Moreover, this work will also focus on the pharmacological modulators of Orai/STIM channel complexes. Together, our thoughtful of the biology and physiology of the Orai/STIM channels have grown remarkably during the past three decades, and the next important milestone in the field of store-operated calcium entry will be to identify potent and selective small molecules as a therapeutic agent with the purpose to target human diseases and disorders for patient benefit.